Urban stream microbial communities show resistance to pharmaceutical exposure. Issue 1 (9th January 2018) - Rosi, E. J.; Bechtold, H. A.; Snow, D.; Rojas, M.; Reisinger, A. J.; Kelly, J. J.
Abstract: Residues of pharmaceuticals are increasingly detected in surface waters throughout the world. In four streams in Baltimore, Maryland, USA, we detected analgesics, stimulants, antihistamines, and antibiotics using passive organic samplers. We exposed biofilm communities in these streams to the common drugs caffeine, cimetidine, ciprofloxacin, and diphenhydramine. Respiration rates in the least urban stream were suppressed when exposed to these drugs, but biofilm functioning in the most urban stream was resistant to drug exposure. Exposure to the antibiotic ciprofloxacin altered bacterial community composition at all sites, with the greatest change occurring in the most urban stream. These results indicated that continuous exposure to drugs in urban streams may select for sub‐populations of highly resistant bacteria that maintain community function in response to urban contaminants.